2021
DOI: 10.3389/fsurg.2021.677799
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Albumin/Globulin Ratio in Patients With Pyogenic Liver Abscess

Abstract: Pyogenic liver abscess (PLA) remains a significant challenge for modern clinicians. Serum albumin/globulin ratio (AGR) can reflect the progress of many diseases. However, the clinical significance of AGR in PLA has not been evaluated. The aim of this study was to explore the effect of AGR on the clinical characteristic and prognosis in PLA patients. This retrospective study included 392 PLA patients who admitted to the First Affiliated Hospital of Xi'an Jiaotong University from January, 2007 to December, 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…In the current investigation, we found that arsenic-exposed fish had low levels of total protein, albumin, and globulin, which may have been caused by proteolysis, a failure in protein synthesis brought on by hepatic and renal dysfunction (Ellis et al, 1981). In arsenic-exposed fish, low level of albumin may represent low blood viscosity, whereas low levels of globulin may be due to the liver inability to synthesized sufficient globulin, an indication of weakened immunity (Zhang et al, 2021). These results are in agreement with those that have been observed after toxicant exposure in several fish species (Kannan et al, 2014;Singh et al, 2015;Ghaffar et al, 2017;Majumder and Kaviraj, 2017;Kumar et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…In the current investigation, we found that arsenic-exposed fish had low levels of total protein, albumin, and globulin, which may have been caused by proteolysis, a failure in protein synthesis brought on by hepatic and renal dysfunction (Ellis et al, 1981). In arsenic-exposed fish, low level of albumin may represent low blood viscosity, whereas low levels of globulin may be due to the liver inability to synthesized sufficient globulin, an indication of weakened immunity (Zhang et al, 2021). These results are in agreement with those that have been observed after toxicant exposure in several fish species (Kannan et al, 2014;Singh et al, 2015;Ghaffar et al, 2017;Majumder and Kaviraj, 2017;Kumar et al, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…In addition, pleural effusion, which develops in approximately 20-50% of patients with PLA, causes considerable distress to patients during treatment [ 31 , 32 , 33 , 34 , 35 ]. The pathophysiology of the development of pleural effusion in patients with PLA is known to result from inflammation of the diaphragm and increased permeability of the lymphatics [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, serum screening tests that can detect physical responses to infection may improve the preoperative diagnostic accuracy of PJI. In various medical fields, serum albumin (Alb) is used as a nutritional indicator and predictive marker for cancer prognosis and infectious diseases [11][12][13]. Recently, the quantitative evaluation of serum Alb and globulin (Glb) levels and the Alb-Glb ratio (AGR) have been reported to be useful in the diagnosis of PJI.…”
Section: Introductionmentioning
confidence: 99%